Psychological sequelae of myocardial infarction - Kumar M.; Nayak P.K. (My University, 2025)
Patient with myocardial infarction (MI) are often affected by psychological disorders such as depression, anxiety, and post-traumatic stress disorder. Psychological disorders are disabling and have a negative influence on recovery, reduce the quality of life and causes high mortality rate in MI patients. Despite tremendous advancement in technologies, screening scales, and treatment strategies, psychological sequelae of MI are currently understudied, underestimated, underdiagnosed, and undertreated. Depression is highly prevalent in MI patients followed by anxiety and post-traumatic stress disorder. Pathophysiological factors involved in psychopathologies observed in patients with MI are sympathetic over-activity, hypothalamic–pituitary–adrenal axis dysfunction, and inflammation. Numerous preclinical and clinical studies evidenced a positive association between MI and psychopathologies with a common molecular pathophysiology. This review provides an update on diagnostic feature, prevalence, pathophysiology, clinical outcomes, and management strategies of psychopathologies associated with MI. Moreover, preclinical research findings on molecular mechanisms involved in post-MI psychopathologies and future therapeutic strategies have been outlined in the review. © 2017 Elsevier Masson SAS